Safety and Efficacy of Heparinization During Mechanical Thrombectomy in Acute Ischemic Stroke - Yang, Ming; Huo, Xiaochuan; Gao, Feng; Wang, Anxin; Ma, Ning; Liebeskind, David S.; Wang, Yongjun; Miao, Zhongrong (Frontiers in Neurology, 2019)
Background The benefits of heparization during mechanical thrombectomy (MT) with newer generation thrombectomy devices, and if it is counterbalanced by the increased risk of intracranial hemorrhage (ICH) remain unknown. Methods We included eligible patients who underwent MT from the ANGEL registry study (2015-2017) in China. Subjects in the current analysis were dichotomized into two groups according to whether adequate heparinization during MT was performed. Safety outcomes (symptomatic intracerebral hemorrhage [sICH], ICH and distal embolization) and efficacy outcomes (artery recanalization and functional outcomes at 3-month follow-up) were compared between groups. Results We included 619 patients from the entire cohort of 917 patients. The average age of them was 63.9±13.7 years, 269 (43.5%) were treated with heparinization during MT. Heparinization during MT didn’t significantly influence recanalization rates, total ICH and long-term mortality (adjusted p>0.05 for all). But sICH and distal embolization occurred more frequently (9.3% vs 5.1%, adjusted p=0.02; 7.1% vs 3.1%, adjusted p=0.04, respectively), while functional independence appeared less likely (39.8% vs 47.4%, adjusted p=0.01) in heparinization group than that in non-heparinization group. Multivariable logistic regression analyses showed that heparinization during MT was an independent predictor for sICH (Odds ratio 2.36 [1.19-4.67], p=0.01) in addition to cardio-embolism stroke and posterior circulation stroke (PCS), and an independent predictor for poor outcome (Odds ratio 1.79 [1.23-2.59], p<0.01) besides age, bridging intravenous thrombolysis, admission NIHSS, drinking and PCS. Conclusion Heparinization during MT may be associated with increased risk of safety outcomes over sICH and distal embolization, as well as efficacy outcomes over long-term poor outcome.